Creating and destroying jobs across East Asia Pacific: A country-level analysis on wages, exports, finance, regulation and infrastructure - Alexander Krauss (IZA Journal of Labor & Development, 2015)
This paper is the first to analyse a much broader range of correlates of job growth simultaneously for each country individually across all 12 East Asian and Pacific countries with stratified randomised enterprise survey data between 2009 and 2012. It acknowledges the strong data limitations and deviates from the standard approach of using pooled, cross-country regressions in analysing enterprise survey data which reduces the usefulness of findings for policymakers in individual countries by neglecting variations across diverse countries with unique business, regulatory and institutional environments. Potential policy responses are derived from the multivariate econometric analyses while highlighting the importance of idiosyncratic country conditions.
Keywords: J21; J24; J30; D22; 330; Employment growth; Job creation; East Asia and Pacific; Enterprise survey; Business climate